2009
DOI: 10.1111/j.1365-2486.2009.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of carbon sequestration on the differential responses of ecosystem photosynthesis and respiration to rain pulses in a semiarid steppe

Abstract: Precipitation pulses play an important role in regulating ecosystem carbon exchange and balance of semiarid steppe ecosystems. It has been predicted that the frequency of extreme rain events will increase in the future, especially in the arid and semiarid regions. We hypothesize that large rain pulses favor carbon sequestration, while small ones cause more carbon release in the semiarid steppes. To understand the potential response in carbon sequestration capacity of semiarid steppes to the changes in rain pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
181
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 51 publications
17
181
3
4
Order By: Relevance
“…The ETs of grazed (3.29 kg m −2 day −1 ), grazing excluded (3.52 kg m −2 day −1 ), and cultivated (3.74 kg m −2 day −1 ) steppe observed in this study were comparable with those found by related research conducted on adjacent Inner Mongolia steppe (Chen et al 2009b;Miao et al 2009). …”
Section: Difference Of Et Compositions Among Different Land Uses Of Ssupporting
confidence: 80%
See 4 more Smart Citations
“…The ETs of grazed (3.29 kg m −2 day −1 ), grazing excluded (3.52 kg m −2 day −1 ), and cultivated (3.74 kg m −2 day −1 ) steppe observed in this study were comparable with those found by related research conducted on adjacent Inner Mongolia steppe (Chen et al 2009b;Miao et al 2009). …”
Section: Difference Of Et Compositions Among Different Land Uses Of Ssupporting
confidence: 80%
“…According to the Chinese classification, soils of the study site are chestnut or chernozem soil (Chen et al 2009b). Xilinhot is located at the northern edge of the Chinese pastoral-farming ecotone (Miao et al 2009;Wu et al 2013), where grazing is the primary land use.…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations